Education in Times of Climate Change for Human Resilience and Environmental Regeneration - Núñez-Rodríguez, José de Jesus (2021)
This article addresses human resilience and environmental regeneration in training the population to adapt and mitigate climate change’s negative effects. The objective is to let teachers know about these constructs’ implications in the behavior of societies in future climate scenarios and the urgent need for their assessment in the classroom. Constructing the essay implied conducting a thorough review of updated bibliography available in indexed journals and documents of international organizations and its subsequent pedagogical contextualization. The analysis allowed concluding that the school should strengthen, in its students, the biological, cognitive, and emotional processes related to resilience to endure uncertain, vulnerable, and complex environments as a result of the occurrence of extreme temperature events (heat and cold waves) and precipitation (droughts, floods, hurricanes). Likewise, education must train future societies to undertake environmental regeneration processes that rebuild the broken tissues of nature as a mechanism to mitigate and compensate for anthropic damages. In these pedagogical scenarios, the school is an institution of the first order to train citizens who will inhabit a planet with environmental conditions and natural resources still unknown to human beings today. Implementing the analyzed constructs requires educational policies, school curricula, and teachers trained to develop them in their classrooms.